Biodegradation of microplastics: optimization and scale up - Paço, Ana Maria Simões do (2019)
Marine litter, specifically small plastic particles, is one of the major threats to the marine ecosystem. The presence of these microplastics has been increasing over the last few years due to their indiscriminate use and lack of polices for their management. Thereby, it is necessary to encounter new ways to mitigate their impacts or even reduce their presence. Biodegradations is a promising solution to this problem. In this work, with the objective of developing a bioremediation process the potential of Zalerion maritimum, to biodegrade polyethylene microplastics, is exploited. Through optimization of the biodegradation medium, by Central composite design and by Uniform design, was possible to obtain higher percentages of microplastics removal and verify that malt extract was the most relevant compost medium to the process. By scale up it was possible to verify that in a less controlled medium the biodegradation of microplastics still occur. In addition, the response of the fungi Zalerion maritimum and Nia vibrissa to exposure to poly(ethylene2,5-furandicarboxylate) has also been studied and it was possible to conclude that these fungi seems to have the capacity of biodegrade this micro(bio)plastic.